Manifestations étranges et espace urbain à Edo - Tadayoshi Uchida (Ebisu: Études Japonaises)
The aim of this article is to demonstrate the existence, within the urban space of Edo (pre-modern Tokyo), of a culture of the strange and the fantastic, closely linked to the city’s geography and topography. Drawing on evidence from the personal notes of civil servants and the literature of the period, the article explores how rumor played a pivotal role in the construction and dissemination of this culture, and how it was anchored in particular places in the city.